Impaired DNA double‐strand breaks repair by kinesin family member 4A inhibition renders human H1299 non‐small‐cell lung cancer cells sensitive to cisplatin. Issue 7 (11th November 2018) - Wan, Qing; Shen, Yong; Zhao, Huzi; Wang, Bei; Zhao, Lei; Zhang, Yongchen; Bu, Xiaodong; Wan, Meiling; Shen, Chuanlu
Abstract: Patients with non‐small‐cell lung cancer (NSCLC) are routinely treated with the platinum‐based chemotherapeutics such as cisplatin. The drug exerts anticancer effects via multiple mechanisms, including DNA double‐strand breaks (DSBs). Enhanced DNA DSB repair capacity would be associated with innate or acquired drug resistance. However, despite strong evidence for the role of the chromokinesin kinesin family member 4A (KIF4A) in DSB repair, the relationship between the chromokinesin and cisplatin sensitivity of human NSCLC cells remains unknown. Furthermore, little is known regarding the effect of targeting KIF4A on the function of DSB repair‐related proteins in these cells. In the current study, we demonstrated that cisplatin treatment stimulated the expression of KIF4A protein in human NSCLC cells. Depletion of KIF4A by small interfering RNA significantly enhanced cisplatin‐induced cell cycle arrest in S and G2/M phases and cytotoxicity in human NSCLC cells. Furthermore, we found that KIF4A inhibition suppressed the ability of cisplatin to induce BRCA2 and Rad51 focus formation and limits the further increase in poly(ADP‐ribose) polymerase 1 activity induced by cisplatin treatment in human NSCLC cells. These studies thus identify the chromokinesin KIF4A as a novel modulator of cisplatin sensitivity that is significantly enhanced by the chromokinesin in human NSCLC cells via multiple mechanisms. Abstract : Cisplatin treatment stimulates the expression of kinesin family member 4A (KIF4A) protein in human non‐small‐cell lung cancer (NSCLC) cells. KIF4A knockdown suppresses the formation of BRCA2 and Rad51 foci and limits the further increase in poly(ADP‐ribose) polymerase 1 activity, thereby enhancing cisplatin‐induced cell cycle arrest in S and G2/M phases and cytotoxicity in human NSCLC cells. KIF4A functions as a novel modulator of cisplatin sensitivity in human NSCLC cells via multiple mechanisms.